О межъязыковых звукосмысловых соответствиях в стихах В. В. Набокова-Сирина [On Some Interlingual Sound Patterns in Vladimir Nabokov’s Poem “La Bonne Lorraine”] - Leonenko, Semyon (Slavica Revalensia, 2014)
This article reveals some anagrammatic patterns in Vladimir Nabokov’s poem “La Bonne Lorraine” (1924). The original Russian text of the poem has several lines that include sound clusters referring to the name of the Maid of Orleans, the heroine of the poem. This poem about Joan of Arc springs from the veryphonetics of its keyword, the sign in absentia (cf., for instance, the very first line, which alludes to the French for Joan, Jeanne: “ZHgli ANglichANe, ZHglimoiu podrugu…”).